2013
DOI: 10.4028/www.scientific.net/amr.772.349
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Graphene/Pd Nanoparticle Composites and their Hydrogen Storage

Abstract: Pd (en)2Cl2can be intercalated into graphite oxide layers with high efficiency. The Pd (en)22+intercalated graphite oxide was firstly synthesized by mixture reaction of Pd (en)2Cl2and graphite oxide, then it was reduced in solution with NaBH4and thereafter the graphene/Pd nanosized particle composites were obtained. The graphene composites were characterized by XRD, FE-SEM, TEM, ICP and N2adsorption tests and their H2storage was also measured. The results show that the composites contain a large amount of Pd a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It has been reported that Pd(NH 3 ) 2 2+ complexion is an excellent precursor for highly efficient preparation of a large number of Pd nanoparticles, where the diameter of Pd particles was 2-6 nm. [33][34][35] Via recycling way Ⅰ, other value metals were still left in the aqueous solution, which is convenient to recycle all value metals respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Pd(NH 3 ) 2 2+ complexion is an excellent precursor for highly efficient preparation of a large number of Pd nanoparticles, where the diameter of Pd particles was 2-6 nm. [33][34][35] Via recycling way Ⅰ, other value metals were still left in the aqueous solution, which is convenient to recycle all value metals respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, they reported an HSC of 3.4 wt% at 77 K and 0.11 MPa. 152 In another study, Zhou et al developed a Pd/graphene nanocomposite using a simple chemical method. 153 In this study, the hydrogen uptake was measured by thermal gravimetric analysis (TGA) in an argon atmosphere and the four different hydrogen storage modes that occur during the reaction were predicted: (i) hydrogen molecule-Pd atom binding; (ii) hydrogen atom-Pd nanoparticle bonding as PdH x hydrides; (iii) atomic hydrogen at the vacant position at graphene; (iv) molecular form hydrogen conned in the perforated graphene substrate.…”
Section: Transition Metal-doped Graphene For Hydrogen Storagementioning
confidence: 99%